The Effectiveness Of Using Mind Mapping Technique To Teach Reading Comprehension - Rahmaida Rahmaida; Ria Kamilah Agustina (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research showed at finding out that the use of mind mapping technique reading comprehension. The research applied pre-experiment research design to the second year students of SMPN 1 Jombang. The sample was the VIII-C chosen by cluster sumpling technique. The data were collected through observation, and test. The data from observation were analyzed descriptively, whereas the data of the test were analyed stastistically. Based on the results of statistical calculations, the results show that there is a significant increase between pretest and posttest scores, the researcher knows that t count is greater than t table (13.140>2,060). By applying 0,05 level of significance with 32 samples. This means that the alternative hypothesis (Ha) i accepted and the hypothesis (Ho) is rejected. So there is a defference in grades VIII-C of SMPN 1 Jombang. It means mind mapping technique was effective.